The roles of school principal: An insight from disadvantaged areas of Indonesia - Ira Mutiaraningrum (UIN Raden Mas Said Surakarta, 2022)
Sequence studies existing have advocated principal’s roles in school development. However, limited study has addressed the principal’s role as educator, manager, administrator, supervisor, leader, innovator, and motivator (EMASLIM) in disadvantaged areas in Indonesia. This current study delves into principals’ efforts and challenges in their previously mentioned roles. For this purpose, a case study was carried out. Involving two participants from two schools in a remote area in Indonesia, this study employed in-depth interviews, WhatsApp chat, WhatsApp voice notes, and documentation for data collection of this study. The findings revealed that the principals focus more on how to deal with the lack of teachers at school so they can carry out their duty as an educator, manager, administrator, supervisor, leader, innovator, and motivator. This study is expected to enrich literature regarding the role of principle, particularly in remote area. Thus, it will help stakeholders in the policy-making that suit the needs of different characteristics. It was found that the main problem is not their location in the remote area, but the lack of quantity and quality of human resources. It seems that the principals shoulder all burden due to the lack of human resources available. This study suggests the government to pay attention to the ratio of teachers and students.